Paradoxically lower prevalence of peripheral arterial disease in South Asians: a systematic review and meta-analysis. Issue 2 (11th June 2013) - Sebastianski, Meghan; Makowsky, Mark J; Dorgan, Marlene; Tsuyuki, Ross T
Abstract : Background: While people of South Asian (SA) descent have higher rates of cardiovascular disease compared with people of White European (WE) descent, a lower prevalence of lower extremity peripheral arterial disease (PAD) has been suggested in SA. Our intent was to systematically review the literature on PAD prevalence in people of SA descent and to conduct a meta-analysis to identify differences in PAD prevalence between SA and WE. Methods: Standard Cochrane systematic review methodology was used for conducting a literature review of published research. Population prevalence studies of PAD in SA with a WE comparison group were included. Full text studies were selected and reviewed by two authors with independent data extraction. Prevalence differences between SA and WE were analysed using ORs. Findings: 129 studies were initially identified and ultimately 15 (n=240 003 patients) studies were included. Only one study reported direct comparative general PAD prevalence between SA and WE (OR=0.26, 95%CI 0.17 to 0.38, p<0.001, n=77 855). Fourteen studies with comparative prevalence data between SA and WE in high-risk populations confirm significantly lower odds of PAD in SA with coronary artery disease (CAD) (OR=0.47, 95%CI 0.39 to 0.56, p<0.001, n=139 313) and diabetes (OR=0.44; 95% CI 0.30 to 0.63, p<0.001, n=22 835). Interpretation: Reported PAD prevalence is significantly lower in SA than WE for both the CAD and diabetes populations. Explanations for these findings, if true, are unclear. These results underscore the need for further study to clarify mechanisms of ethnic divergence in PAD prevalence.